2007
DOI: 10.1099/mic.0.2007/010926-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncultivated Tannerella BU045 and BU063 are slim segmented filamentous rods of high prevalence but low abundance in inflammatory disease-associated dental plaques

Abstract: Uncultivated clones BU045 and BU063 and Tannerella forsythia, a 'consensus periodontal pathogen', are the closest known relatives within the genus Tannerella. They have been described to inhabit different ecological niches of the human oral cavity. In this study, fluorescent in situ hybridization (FISH) and immunofluorescence were combined to investigate the prevalence and abundance of BU045 and BU063 in comparison to T. forsythia in plaques from gingivitis, necrotizing ulcerative gingivitis (NUG) and chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 43 publications
(39 reference statements)
2
37
0
Order By: Relevance
“…OT286, an uncultivated phylotype that has been frequently identified in periodontal health [24] in contrast to its close relative Tannerella forsythia , one of the most important periodontal pathogens. To try to isolate this organism we singled out species that were present at least in both clusters from healthy biofilms and if possible had a direct link to Tannerella sp.…”
Section: Resultsmentioning
confidence: 99%
“…OT286, an uncultivated phylotype that has been frequently identified in periodontal health [24] in contrast to its close relative Tannerella forsythia , one of the most important periodontal pathogens. To try to isolate this organism we singled out species that were present at least in both clusters from healthy biofilms and if possible had a direct link to Tannerella sp.…”
Section: Resultsmentioning
confidence: 99%
“…HOT-286 (Leys et al 2002;de Lillo et al 2004;Zuger et al 2007). Although it was reported that Tannerella sp.…”
Section: Discussionmentioning
confidence: 99%
“…HOT-286 is found in high prevalence but low abundance in periodontal disease-associated plaques (Zuger et al 2007), and the relative abundance of this phylotype is estimated to be around 0.05% of subgingival bacteria (Human Oral Microbiome Database, release 13; Beall et al 2014). Evidence from several studies has indicated that, unlike T. forsythia, Tannerella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking increases the risk of periodontitis and levels of periodontal pathogens such as P. gingivalis and A. actinomcytemcomitans . Using 16S rRNA analysis, several species of Fusobacteria, Peptostreptococcus, Prevotella, Capnocytophaga, Eikenella and Porphyromonas are found to be distributed differently between healthy and diseased sites on teeth (105109). There is some evidence for racial differences in periodontal pathogens; P.gingivalis and P. anaerobius were more significantly associated with black subjects in the adult periodontitis group, while F. nucleatum was associated with white subjects in both the adult periodontitis and early onset periodontitis groups (110).…”
Section: Oral Flora and Ptbmentioning
confidence: 99%